MARFISH and HYDRO : Pengembangan Program Kreativitas Mahasiswa Kewirausahaan - Fuadi; Falahuddin; Arlianyah; Hasan, Nazli; Fauzan, Asrul; Mufid, Muhammad Nuzul; Hermawan, Riski (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This research proposes innovation in farming and animal husbandry by integrating hydroponic systems and catfish cultivation on limited land. With a focus on the North Aceh Utara, research created MARFISH AND HYDRO, a catfish farm using tarpaulin media in a hydroponic system. This research aims to produce satisfactory results, protect the environment from pollution, and provide multiple benefits on limited land. Through market survey steps, feasibility studies, production processes, and marketing, this research creates sustainable methods in fish cultivation and hydroponic farming. With competitive prices and promotions through social media and banner installation, MARFISH AND HYDRO is expected to be able to meet market demand and make a positive contribution to the local economy. This research also explores the potential for business development, including the production of processed catfish, such as catfish chips and catfish pecel. The research results show success in carrying out the cultivation process, marketing, and the potential for business expansion to achieve long-term goals.